Dupuytren contracture in a patient with congenital camptodactyly and incidental Carpal Tunnel Syndrome. - Subramaniam, Mahendran; Hussin, Paisal; Ng, Eng Seng; Tunku Ahmad Yahaya, Tunku Sara (Malaysian Orthopaedic Association, 2008)
Dupuytren contracture is commonly seen in northern European populations but not in Asians. Even more rare is a presentation of flexion deformity of fingers involving two different pathologies with incidental carpal tunnel syndrome in the same patient. We report herein a case of Dupuytren contracture with congenital camptodactyly and unilateral carpal tunnel syndrome.